2019
DOI: 10.1371/journal.pone.0220318
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy examination of red blood and yeast cell agglutination induced by bacterial lectins

Abstract: Lectins are a group of ubiquitous proteins which specifically recognize and reversibly bind sugar moieties of glycoprotein and glycolipid constituents on cell surfaces. The mutagenesis approach is often employed to characterize lectin binding properties. As lectins are not enzymes, it is not easy to perform a rapid specificity screening of mutants using chromogenic substrates. It is necessary to use different binding assays such as isothermal titration calorimetry (ITC), surface plasmon resonance (SPR), micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Thus, MST offers an accurate and convenient method for quantifying aptamer binding affinity. 24,25 MST analyses indicated that most inosinecontaining aptamers bound cocaine with a higher affinity than their unmodified counterparts (Table 1, Figure 2a). The Finally, the 38-GC G 25 substitution, 38-IC, showed an impressive 63-fold increase in affinity compared to the parent 38-GC aptamer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, MST offers an accurate and convenient method for quantifying aptamer binding affinity. 24,25 MST analyses indicated that most inosinecontaining aptamers bound cocaine with a higher affinity than their unmodified counterparts (Table 1, Figure 2a). The Finally, the 38-GC G 25 substitution, 38-IC, showed an impressive 63-fold increase in affinity compared to the parent 38-GC aptamer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mannose residues exist as a core component of fungal cell wall mannans and mannoproteins, and therefore are present across all morphologies of C. albicans [ 70 72 ]. Yeast agglutination assays are used to detect and study sugar-specificities of lectin activity such as of type I fimbriae [ 73 76 ]. As a proxy for C. freundii adhesion to C. albicans within our model, we used C. albicans yeast agglutination by C. freundii cell suspensions to determine that C. albicans–C.…”
Section: Resultsmentioning
confidence: 99%
“…When adding SaroL-1 to rabbit red blood cells, hemolysis was observed instead of hemagglutination classically induced by multivalent lectins 40 . The hemolysis was confirmed by measuring the absorbance at 540 nm (Fig.…”
Section: Resultsmentioning
confidence: 89%